Expression of lymphatic markers and lymphatic growth factors in psoriasis before and after anti-TNF treatment - Aikaterini Evangelia Moustou; Paraskevi Alexandrou; Alexander J Stratigos; Ioanna Giannopoulou; Theognosia Vergou; Andreas Katsambas; Christina Antoniou (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: Angiogenesis is an early stage of psoriatic lesion development, but less is known about lymphagiogenesis and its role in the development of psoriasis. OBJECTIVE: To examine the expression of specific lymphatic markers and lymphatic growth factors in untreated psoriatic skin, in the unaffected skin of patients and skin of healthy volunteers, as well as their alteration after treatment with an anti-TNF agent. METHODS: Immunohistochemistry for the lymphatic markers D2-40 and LYVE-1, in addition to the VEGF-C and VEGF-D growth factors, was performed in the skin biopsies of psoriatic lesions and adjacent non-psoriatic skin of 19 patients before and after treatment with etanercept, as well as in the skin biopsies of 10 healthy volunteers. RESULTS: The expressions of D2-40, VEGF-C and VEGF-D on lymphatic vessels underwent statistically significant increases in untreated psoriatic skin compared with non-lesional skin, in contrast to LYVE-1, which did not involve significant increase in expression in psoriatic skin. VEGF-C expression on lymphatic vessels diminished after treatment with etanercept. Moreover VEGF-C and VEGF-D staining on fibroblasts presented with higher expression in lesional skin than in non-lesional adjacent skin. CONCLUSION: Remodeling of lymphatic vessels possibly occurs during psoriatic lesion development, parallel to blood vessel formation. The exact role of this alteration is not yet clear and more studies are necessary to confirm these results.